An Analysis upon Various Aspects of Metric Spaces in Real Analysis: Some Solutions: Exploring the beauty of metric spaces in real analysis and its applications (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper will introduce the reader to the concept of metrics and metric spaces. A lot emphasis has been given to motivate the ideas under discussion to help the reader develop skill in using his imagination to visualize the abstract nature of the subject. Variety of examples along with real life applications have been provided to understand and appreciate the beauty of metric spaces.